PF-3 Prevalence and Risk Factors of Jembrana Disease, Bengkalis District Riau Province - Hani Muhamad Mardani; Dewi Anggreini; Yuli Miswati; Heru Susetya (Hemera Zoa, 2018)
Jembrana disease (JD) is contagious viral disesase in Bali cattle, caused by Retrovirus from member of Lentivirus group called by Jembrana disease virus (JDV). Jembrana disease outbreak in Bengkalis district first occured 2013 and until now is endemic. This purpose of study is to determine the prevalence of JD and to identify a risk factor associated with JD in Bengkalis district.